2019
DOI: 10.5194/acp-19-10717-2019
|View full text |Cite
|
Sign up to set email alerts
|

Core and margin in warm convective clouds – Part 1: Core types and evolution during a cloud's lifetime

Abstract: Abstract. The properties of a warm convective cloud are determined by the competition between the growth and dissipation processes occurring within it. One way to observe and follow this competition is by partitioning the cloud to core and margin regions. Here we look at three core definitions, namely positive vertical velocity (Wcore), supersaturation (RHcore), and positive buoyancy (Bcore), and follow their evolution throughout the lifetime of warm convective clouds. Using single cloud and cloud field simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…In this model, the convective cloud "core" associated with updraft motion and increased condensate loading is located in the geometrical center of the cloud, surrounded by the cloud "shell" associated with downdrafts and condensate evaporation. The core-shell model is supported by multiple observational studies (e.g., Heus et al, 2009;Rodts et al, 2003;Wang et al, 2009) and numerical modeling investigations (e.g., Heus and Jonker, 2008;Jonker et al, 2008;Seigel, 2014) and hence represents the essence of several convection parameterizations. Heiblum et al (2019) showed that the core-shell model is valid for about 90 % of the typical cloud's lifetime, with the largest discrepancy from the assumed core-shell geometry occurring during the dissipation stage of the cloud.…”
Section: Shallow Cumulus Cloudsmentioning
confidence: 93%
See 2 more Smart Citations
“…In this model, the convective cloud "core" associated with updraft motion and increased condensate loading is located in the geometrical center of the cloud, surrounded by the cloud "shell" associated with downdrafts and condensate evaporation. The core-shell model is supported by multiple observational studies (e.g., Heus et al, 2009;Rodts et al, 2003;Wang et al, 2009) and numerical modeling investigations (e.g., Heus and Jonker, 2008;Jonker et al, 2008;Seigel, 2014) and hence represents the essence of several convection parameterizations. Heiblum et al (2019) showed that the core-shell model is valid for about 90 % of the typical cloud's lifetime, with the largest discrepancy from the assumed core-shell geometry occurring during the dissipation stage of the cloud.…”
Section: Shallow Cumulus Cloudsmentioning
confidence: 93%
“…This knowledge will be exploited later when constructing the Tripleclouds radiation scheme. Shallow cumulus clouds are convective clouds, which are often treated with the "coreshell model" (Heus and Jonker, 2008;Heiblum et al, 2019). In this model, the convective cloud "core" associated with updraft motion and increased condensate loading is located in the geometrical center of the cloud, surrounded by the cloud "shell" associated with downdrafts and condensate evaporation.…”
Section: Shallow Cumulus Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge will be exploited later when constructing the Tripleclouds radiation scheme. Shallow cumulus clouds are convective clouds, which are often treated with the "core-shell model" (Heus and Jonker, 2008;Heiblum et al, 2019). In this model the convective "cloud core" associated with updraft motion and increased condensate loading is located in the geometrical centre of the cloud, surrounded by the "cloud shell" associated with downdrafts and condensate evaporation.…”
mentioning
confidence: 99%
“…The core-shell model is supported by multiple observational studies (e.g., Heus et al, 2009;Rodts et al, 2003;Wang et al, 2009) and numerical modelling investigations (e.g., Heus and Jonker, 2008;Jonker et al, 2008;Seigel, 2014) and hence represents the essence of several convection parametrizations. Heiblum et al (2019) showed that the core-shell model is valid for about 90 % of the typical cloud's lifetime, with the largest discrepancy from the assumed core-shell geometry occurring during the dissipation stage of the cloud. Whereas most of the clouds contain a single core, larger clouds can possess multiple cores.…”
mentioning
confidence: 99%